Pengaruh Lingkungan, Motivasi dan Kepuasan Kerja Terhadap Kinerja Karyawan Perusahaan Retail di Jakarta - Leli Lestariani Lahagu; Achmad Tarmizi; Didin Hikmah Perkasa (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to determine and analyze the effect of Environment, Work Motivation and Job Satisfaction on Employee Performance of Retail Companies in Jakarta. The research design uses causal quantitative methods, namely knowing the effect between the variables studied. The data collection tool uses a questionnaire that has been tested for validity and reliability which is distributed via googleform to employees of retail companies in Jakarta. The population studied in this study were 60 people, while the sample used was 60 people using saturated sampling technique. Data analysis was carried out using SPSS to test validity, reliability and multiple linear regression... The first stage of making a research instrument for each variable studied, namely work environment, work motivation, job satisfaction and employee performance ... The second stage tested the validity and reliability of each variable. The results showed passively that the work environment, work motivation and job satisfaction affect the performance of retail company employees in Jakarta.